OP535 Cost-Effectiveness Of Internet-Based HIV Screening In Men Who Have Sex With Men in Vancouver, British Columbia, Canada. (December 2020) - Zhang, Wei; de Anda, José; Irvine, Michael; Chang, Hsiu-Ju; Gilbert, Mark
Abstract : Introduction: In Canada, individuals test for HIV commonly through clinic-based screening services (CBSS). However, gay, bisexual and other men who have sex with men (GBMSM) may face barriers accessing such services due to, for example, feeling discomfort disclosing their sexual history or fearing judgment from healthcare providers. To reduce barriers and increase uptake and frequency of screening for sexually-transmitted infections (STIs) including HIV, the British Columbia Centre for Disease Control implemented an internet-based screening service, GetCheckedOnline.com (GCO), in September 2014 in Vancouver, Canada. We assessed the cost-effectiveness of GCO at different uptake scenarios compared to CBSS in Vancouver GBMSM. Methods: Cost-utility analyses were conducted from a healthcare payer's perspective using an established dynamic GBMSM HIV compartmental model. The model estimated the probability of becoming infected with HIV, progressing through diagnosis, disease stages, and treatment over a 30-year time horizon. The base case assumed 4.7 percent uptake of GCO, and 74 percent of high-risk and 44 percent of low-risk infrequent testers becoming regular testers in five years. Scenario analyses tested GCO 10 and 15 percent uptakes. Results: Compared with the conventional CBSS alone, a 4.7 percent GCO uptake increased the costs by CAD90, 059 (USD75, 680; 95% confidence interval (CI): -CAD420, 836, CAD273, 987) and gained 3 (95% CI: 0, 6) quality-adjusted life years (QALYs) in a 30-year time horizon. There was a 71 percent probability that GCO was cost-effective at a cost-effectiveness threshold of CAD50, 000 (USD42, 000) per QALY. The results were consistent in other two uptake scenarios. Conclusions: Expanding HIV screening for GBMSM through increasing uptake of GCO is a cost-effective alternative to expanding the conventional CBSS. We noted that difference in total costs might be smaller if a battery of STI tests is considered, which in turn may affect our cost-effectiveness estimate. For the next phase of cost-utility analysis, we will expand our model to include testing for other STIs.